2003
DOI: 10.1046/j.1365-2702.2003.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication calculation skills of nurses in Finland

Abstract: The aim of this study was to describe the medication calculation skills of nurses in Finland. We tried to ascertain how nurses evaluate their own medication calculation skills and how these self-evaluations are associated with various background factors and the actual level they score in a calculation test. In the spring of 2000, nurses (n = 546) in one Finnish university hospital completed a questionnaire specially developed for this study. The instrument included structured questions, statements and a medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 26 publications
3
46
1
3
Order By: Relevance
“…The inability to identify an error has been documented in the literature and has been replicated within this study with students not identifying their unreasonable answers as perhaps being incorrect, therefore highlighting a lack of conceptual understanding. [12] These results were produced in a classroom environment with all of the situational stressors of a real time patient care setting removed. When considering these results alongside the results produced in previous studies, calculation and drug administration error is not only real but likely to occur in approximately half of all dosage calculations, thereby potentially putting the patient at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inability to identify an error has been documented in the literature and has been replicated within this study with students not identifying their unreasonable answers as perhaps being incorrect, therefore highlighting a lack of conceptual understanding. [12] These results were produced in a classroom environment with all of the situational stressors of a real time patient care setting removed. When considering these results alongside the results produced in previous studies, calculation and drug administration error is not only real but likely to occur in approximately half of all dosage calculations, thereby potentially putting the patient at risk.…”
Section: Discussionmentioning
confidence: 99%
“…The fi nal type is computational errors involve miscalculation of simple functions such as multiplication, division, subtraction or addition. [9][10][11][12][13][14] In Victoria, Australia, the fi nal two years of secondary schooling form the graduation requisites of the Victorian Certificate of Education (VCE). During the VCE there are three levels of mathematics in each of the final two years of secondary schooling.…”
Section: Methodsmentioning
confidence: 99%
“…18 Several studies and reports demonstrate the need to make mathematical calculations a priority focus area. 19,20 More than 1 in 6 medication errors involve a calculation error. [21][22][23] A simulated study in a pediatric stabilization unit in England found that 14.2% of 150 orders were converted from milligrams to milliliters incorrectly, with a maximum dose deviation of 400%.…”
Section: Principles Of Safe Medication Administrationmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15] The inability to perform accurate calculations may result in a compromise of patient safety which may lead to an under-dosing, overdosing, or a major adverse event such as death.…”
Section: Introductionmentioning
confidence: 99%
“…[2,5,14,[17][18][19] In the out-of-hospital environment paramedics face additional distractions which may be caused by loud noise, poor lighting, hot and cold weather extremes, a life threatening situation with a child, pressure from relatives, bystanders, and a lack of resources compared to the hospital setting. [20] Previous studies into the ability of paramedics to perform calculations without the aid of a calculator have identified low levels of accuracy with mean scores between 40% and 65%.…”
Section: Introductionmentioning
confidence: 99%